Effects of Intangible Cultural Heritage for Economic Development in Nepal - Dhakal, Chandra Prasad (NUTA Journal, 2023)
Nepal is the land of diverse culture and rituals that play vital role on tourism development. In Nepal, cultural tourism has vital role on tourism development like natural diversities. In cultural tourism, intangible cultural heritage (ICH) like festivals, rituals and customs, craftsmanship, music, dance of different castes and ethnic comminutes play important role for tourism promotion. The objectives of the study are to analyze how ICH play's role on economic development through tourism and why ICH is important for a nation enhance overall economic activities. The study followed qualitative research design and draw the conclusion on the basis of primary and secondary sources of the data collected. Primary data were collected from Kathmandu valley Basantapur area and secondary data were gathered from books, articles and various documents related to the study area. Findings and conclusion of the study has been based on description and analysis of the data. Countries like Nepal, ICH can support for economic enhance through various ways such as increasing demand of the goods, increasing the attraction of tourists in sites, increasing expenditure of the festival's organizers.